Rethinking body language in terms of power relations - Adeline Paxton (Communicare)
The paper will examine power relations via body language, as an as pact of non-verbal communication. Studies of body language aries within such divergent (and often leo lated) disciplines as semiotics, pay. chology, and performance studies, while published works are further divided between the popular and the scientific. Popular works are often accused of being simplistic, while many of the specialised scientific works on non-verbal communication ignore the wider social context in which body language occurs. Because the Cultural Studies approach explicitly links power rela tions and communication, it is able to offer a framework in which dis parate threads from different discl plines can be drawn together to fa cilitate a broader understanding of body language. Body language is thus as Important a tool of the Cul tural Studies project. It comple ments other aspects of communication studies, which have hitherto tended specifically to concentrate on studies of television, radio, news papers, film, magazines and other media, or on studies of Interper sonal communication